Bisphophonates in CKD Patients with Low Bone Mineral Density - Wen-Chih Liu; Jen-Fen Yen; Cheng-Lin Lang; Ming-Tso Yan; Kuo-Cheng Lu (The Scientific World Journal)
Patients with chronic kidney disease-mineral and bone disorder (CKD-MBD) have a high risk of bone fracture because of low bone mineral density and poor bone quality. Osteoporosis also features low bone mass, disarranged microarchitecture, and skeletal fragility, and differentiating between osteoporosis and CKD-MBD in low bone mineral density is a challenge and usually achieved by bone biopsy. Bisphosphonates can be safe and beneficial for patients with a glomerular filtration rate of 30 mL/min or higher, but prescribing bisphosphonates in advanced CKD requires caution because of the increased possibility of low bone turnover disorders such as osteomalacia, mixed uremic osteodystrophy, and adynamic bone, even aggravating hyperparathyroidism. Therefore, bone biopsy in advanced CKD is an important consideration before prescribing bisphosphonates. Treatment also may induce hypocalcemia in CKD patients with secondary hyperparathyroidism, but vitamin D supplementation may ameliorate this effect. Bisphosphonate treatment can improve both bone mineral density and vascular calcification, but the latter becomes more unlikely in patients with stage 3-4 CKD with vascular calcification but no decreased bone mineral density. Using bisphosphonates requires considerable caution in advanced CKD, and the lack of adequate clinical investigation necessitates more studies regarding its effects on these patients.